Keterkaitan antar Faktor Penyebab Pembengkakan Biaya pada Proyek Transportasi dengan Kontrak Tahun Jamak - Faslan Syam Sajiah (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2022)
ABSTRACT To boost its economy, the Government of Indonesia invests heavily in transportation infrastructure. Government infrastructure projects face cost overruns that can lead to negative economic growth, waste of limited resources, prolonged project completion time, lead to negative public perceptions, disputes, litigation, and project abandonment. This study aims to identify the root causes of cost overruns for transportation infrastructure projects implemented under Multi-Year Contracts in Indonesia. The causes of cost overruns are described in the cognitive map to determine the causal relationship between factors. Changes in government regulations, unexpected subsurface conditions, delayed land acquisition, and financial problems by the owner are the root causes of cost overruns in the construction of the Kendari Bay Bridge which is the object of the research case study. The results of this study can assist project owners, contractors, and consultants in understanding the causes of cost overruns, so that each party, especially ministries and agencies as project owners, can identify these factors so that the risk can be mitigated.  Keywords: case study, cognitive map, Indonesia, infrastructure, transportation, budgeting